From imagery to ecology: leveraging time series of all available Landsat observations to map and monitor ecosystem state and dynamics. Issue 3 (1st September 2016) - Pasquarella, Valerie J.; Holden, Christopher E.; Kaufman, Les; Woodcock, Curtis E.
Abstract: With over 30 years of directly comparable Landsat satellite observations now freely available, and new imagery being added to the Landsat archive every day, Landsat time series analysis affords novel opportunities for ecosystem mapping, environmental monitoring and comparative ecology. This study presents a series of data‐driven examples that illustrate the potential of using Landsat time series to further the study of land cover characterization, vegetation phenology and landscape dynamics. Our goal is to showcase how ecosystem properties and dynamics manifest in the Landsat data record, laying the foundation for better integration of remote sensing and ecology using Landsat time series. Our results suggest that time series provide valuable information on ecosystem cover, use and condition that could advance understanding of ecosystem function, resilience and dynamics. We have only just begun to understand how to use the complete record of Landsat observations for the study of ecology, and we hope this work will encourage future studies on quantifying and analyzing relationships between time series data, ecosystems and ecological processes. Abstract : With over 30 years of directly comparable Landsat satellite observations now freely available, and new imagery being added to the Landsat archive every day, Landsat time series analysis affords novel opportunities for ecosystem mapping, environmental monitoring and comparative ecology. This study presents a series of examples that illustrate the potential of using Landsat time series to further the study of land cover characterization, ecosystem phenology, landscape dynamics and large‐scale ecological gradients.